The Potential Role of Naringin and Naringenin as Nutraceuticals Against Metabolic Syndrome - Massaro, Luca; Raguzzini, Anna; Aiello, Paola; Valencia, Débora Villaño (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Metabolic syndrome, an increasing problem in western society, is a cluster of conditions that affect cardiovascular health, lipid and glucose management, increasing the risk of heart diseases, stroke and diabetes. Bioactive flavonoids are a great resource of compounds with proven antiinflammatory activities. Naringin, a natural flavanone found in citrus fruits, and its aglycone have demonstrated to ameliorate obesity, dyslipidemia, and insulin resistance in animal models. The principal mechanisms by which these flavonoids exert their action involve AMPK and PPARα up-regulation and the down-regulation of genes involved in lipid metabolism. Although different studies have been carried out to define the pharmacological effects of these flavonoids, their therapeutic use is still limited.
Keywords: metabolic syndrome